Nuevas citas para la flora vallisoletana. II. - Lázaro Bello, Jesús Antonio (Acta Botanica Malacitana, 2003)
New floristic records for Valladolid province. II Palabras clave. Corología, flora vascular, España, Valladolid. Key words. Chorology, vascular flora, Spain, Valladolid.